Quality of health care around the time of childbirth during the COVID‐19 pandemic: Results from the IMAgiNE EURO study in Norway and trends over time. Issue 1 (18th December 2022) - Nedberg, Ingvild Hersoug; Vik, Eline Skirnisdottir; Kongslien, Sigrun; Mariani, Ilaria; Valente, Emanuelle Pessa; Covi, Benedetta; Lazzerini, Marzia; ,
Abstract: Objective: To describe maternal perception of the quality of maternal and newborn care (QMNC) in facilities in Norway during the first year of COVID‐19 pandemic. Methods: Women who gave birth in a Norwegian facility from March 1, 2020, to October 28, 2021, filled out a structured online questionnaire based on 40 WHO standards‐based quality measures. Quantile regression analysis was performed to assess changes in QMNC index over time. Results: Among 3326 women included, 3085 experienced labor. Of those, 1799 (58.3%) reported that their partner could not be present as much as needed, 918 (29.8%) noted inadequate staff numbers, 183 (43.6%) lacked a consent request for instrumental vaginal birth (IVB), 1067 (34.6%) reported inadequate communication from staff, 78 (18.6%) reported fundal pressure during IVB, 670 (21.7%) reported that they were not treated with dignity, and 249 (8.1%) reported experiencing abuse. The QMNC index increased gradually over time (3.68 points per month, 95% CI, 2.83–4.53 for the median), with the domains of COVID‐19 reorganizational changes and experience of care displaying the greatest increases, while provision of care was stable over time. Conclusion: Although several measures showed high QMNC in Norway during the first year of the COVID‐19 pandemic, and a gradual improvement over time, several findings suggest that gaps in QMNC exist. These gaps should be addressed and monitored. Synopsis: Women who gave birth in Norway during the first year of the COVID‐19 pandemic did not receive optimal care during their hospital stay.